2006
DOI: 10.1080/00049180500511962
|View full text |Cite
|
Sign up to set email alerts
|

Everyday Water: cultures in transition

Abstract: In this paper we will present the Everyday Water project as a case study of recent cultural research on domestic water use and its application to natural resource policy and practice. This project is innovative not only because it is a research partnership between a development company and a university but also because of the cultural research approach the project brings to the issue of water resource sustainability and management. The Everyday Water project moves away from thinking of water as a discrete reso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
134
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 158 publications
(144 citation statements)
references
References 4 publications
9
134
1
Order By: Relevance
“…However, they have not compared this with communities not subject to water use restrictions (Friend and Coutts 2006;Marks et al 2008;Randolph and Troy 2007). Allon and Sofoulis (2006) conducted cultural research on domestic water use in Sydney Australia, a city which has been subject to water use restrictions. The authors found that while participants of the study were found to take personal measures to save water, they were "largely stuck within current socio-technological systems".…”
Section: The Effect Of Environmental / Locational Characteristics On mentioning
confidence: 99%
See 2 more Smart Citations
“…However, they have not compared this with communities not subject to water use restrictions (Friend and Coutts 2006;Marks et al 2008;Randolph and Troy 2007). Allon and Sofoulis (2006) conducted cultural research on domestic water use in Sydney Australia, a city which has been subject to water use restrictions. The authors found that while participants of the study were found to take personal measures to save water, they were "largely stuck within current socio-technological systems".…”
Section: The Effect Of Environmental / Locational Characteristics On mentioning
confidence: 99%
“…Further research is required to explore actual behaviour change resulting from restrictions and other policy interventions. Various authors have discussed the effect media campaigns can have on people's attitudes to alternative water sources (Allon and Sofoulis 2006;Coutts 2006;Dishman et al 1989;Friend and Coutts 2006;Marks et al 2008;Po et al 2003). However, none of these studies have measured the effect those campaigns have had on actual water use behaviour.…”
Section: The Effect Of Marketing Interventions On Water-related Behavmentioning
confidence: 99%
See 1 more Smart Citation
“…A survey of Australian households found that the least affluent households were most adept at creatively changing household practices to reduce energy, fuel, water and food consumption (Waitt et al 2012). In other studies, ethnic minority/migrant households were found to engage in sustainable practices, using public transport at above-average rates and saving water (Allon and Sofoulis 2006). In a qualitative study, Strengers and Maller (2012) observed that many migrants were adept at saving water and energy due to pre-migration experiences of resource scarcity, service disruption, and familiarity with manual water collection and treatment practices.…”
Section: Implication 3: Unheralded Capacitiesmentioning
confidence: 99%
“…From a social science perspective, a core problematic of understanding water demand is the difficulty of making visible the inconspicuous, taken for granted water consumption and waste water production embedded in the use of infrastructures and technologies in the modern home, and the connections of this demand to current and shifting urban infrastructure (Kaika and Swyngedouw 2000;Sofoulis 2005;Allon and Sofoulis 2006;Shove 2003;Hand et al 2005;Kaika 2004;Geels 2005). This inconspicuous consumption becomes particularly concerning for a sector seeking to anticipate the challenges of climatic change in combination with other population, cultural and technological changes.…”
Section: The Importance Of Letting Go Of Watermentioning
confidence: 99%